Synthesis and Optical Characterization of Ag/PVA Nanocomposites Films - Salloom, Hussein T; Jasim, Aseel S; Hamad, Tagreed K (Al-Nahrain Journal of Science, 2017)
ilver- Poly vinyl alcohol Ag/ PVA nanocomposite films were prepared by casting method at room temperature with different amount of AgNO3 solution (0.001, 0.0015, and 0.002ml). The prepared nanocomposites were characterized using UV–VIS spectrophotometer and the optical properties were investigated in the wavelength range 300-800 nm. The absorption peaks showed a shift towards higher wavelength with increasing AgNO3 concentration while the energy band gap and absorption edges shifted towards lower energies with the increase of AgNO3 concentration.